Developing a Computer Simulation Game as a Training Tool for Mine Self-Escape in Underground Coal Mine - Hendra Harisman; Phillip Stothard; Nurul Aflah (Graduate Program of Syiah Kuala University, 2021)
– Gaming technology has been growing these years rapidly. The game engines have the capability of creating a very realistic virtual environment model. This technology can also be used for mining purposes. In this research, the game engine is specifically used to develop a mine self-escape simulation game for training purposes. The game engine which is used to develop the simulation game is Unreal Engine 3. The main advantage of using such a simulation game as a training tool is because it allows the trainee to experience a dangerous situation while not being put in danger. This kind of training is considered better than conventional briefing, normally conducted by showing a video or pamphlet. Studies have shown that people retain more information when they are involved interactively in the learning process. In this research, a computer simulation game as a training tool for underground coal mine self-escaped has been successfully created using fire scenarios. The player/trainee should follow some procedures to get to the safety zone